2012
DOI: 10.1187/cbe.11-04-0040
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Biological Consequences of Alcohol Abuse through an Online Game: Impacts among Secondary Students

Abstract: A multimedia game was designed to serve as a dual-purpose intervention that aligned with National Science Content Standards, while also conveying knowledge about the consequences of alcohol consumption for a secondary school audience. A tertiary goal was to positively impact adolescents' attitudes toward science through career role-play experiences within the game. In a pretest/delayed posttest design, middle and high school students, both male and female, demonstrated significant gains on measures of content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
3
33
1
Order By: Relevance
“…The high acceptability ratings for the game are encouraging for further research on the ability of ''Fitter Critters'' to improve healthy eating and activity. Studies of health videogames used in school to increase health knowledge reported satisfaction and usability ratings ranging from 3.39 to 3.75 on a 5-point scale, 10,11 which is lower than the mean ratings observed in the present study. As satisfaction and usability appear to be correlated with knowledge gained, the high acceptability of ''Fitter Critters'' has implications for its ability to impact health knowledge and ultimately behavior.…”
contrasting
confidence: 97%
See 3 more Smart Citations
“…The high acceptability ratings for the game are encouraging for further research on the ability of ''Fitter Critters'' to improve healthy eating and activity. Studies of health videogames used in school to increase health knowledge reported satisfaction and usability ratings ranging from 3.39 to 3.75 on a 5-point scale, 10,11 which is lower than the mean ratings observed in the present study. As satisfaction and usability appear to be correlated with knowledge gained, the high acceptability of ''Fitter Critters'' has implications for its ability to impact health knowledge and ultimately behavior.…”
contrasting
confidence: 97%
“…The health meter changes based on the Critter's diet and physical activity. The diet meters represent daily nutritional requirements, based on the USDA recommendations for children [8][9][10][11][12] years old, and fill as the player feeds the Critter. Meters reset daily so they can be filled again the next time the player logs on.…”
Section: Meters the Game Displays Meters Representing Thementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the game employs a theme of a typical night out whereby gamers' choices regarding drinking result in a positive or negative outcome. In America, Klisch, Miller, Beier, and Wang (2012) developed a multimedia digital game, The Web Adventure, N Squad, which incorporated middle school health content and effects of alcohol consumption. The purpose of the game was to simultaneously educate teenagers about alcohol abuse while impacting positively on their attitudes toward science.…”
Section: Social Marketing and Alcohol Consumptionmentioning
confidence: 99%